Dementia alters standing postural adaptation during a visual search task in older adult men. (23rd April 2015) - Jor'dan, Azizah J.; McCarten, J. Riley; Rottunda, Susan; Stoffregen, Thomas A.; Manor, Brad; Wade, Michael G.
Highlights: We examine the effects of dementia on postural adaptation during visual search. Dementia influences overall standing postural sway. Postural adaptation correlates with task performance only in those non-demented. Dementia alters the ability to adapt one's posture to a visual search task. The perception-action synergy may serve as a novel assessment for dementia. Abstract: This study investigated the effects of dementia on standing postural adaptation during performance of a visual search task. We recruited 16 older adults with dementia and 15 without dementia. Postural sway was assessed by recording medial–lateral (ML) and anterior–posterior (AP) center-of-pressure when standing with and without a visual search task; i.e., counting target letter frequency within a block of displayed randomized letters. ML sway variability was significantly higher in those with dementia during visual search as compared to those without dementia and compared to both groups during the control condition. AP sway variability was significantly greater in those with dementia as compared to those without dementia, irrespective of task condition. In the ML direction, the absolute and percent change in sway variability between the control condition and visual search (i.e., postural adaptation) was greater in those with dementia as compared to those without. In contrast, postural adaptation to visual search was similar between groups in the AP direction. As compared to those without dementia, those with dementia identified fewer letters on the visual task. In the non-dementia group only, greater increases in postural adaptation in both the ML and AP direction, correlated with lower performance on the visual task. The observed relationship between postural adaptation during the visual search task and visual search task performance—in the non-dementia group only—suggests a critical link between perception and action. Dementia reduces the capacity to perform a visual-based task while standing and thus, appears to disrupt this perception-action synergy.